THE EFFECT OF TRANSFER DISTANCE TO LOWER BACK TWISTING AND BENDING PATTERNS IN MANUAL TRANSFER TASK (Jurnal Teknologi (Sciences & Engineering), 2021)
Manual material handling (MMH) activities utilize human’s effort with minimal aid from mechanical devices. MMH is typically associated with poor lower back posture which can lead to lower back injury. The likelihood to develop musculoskeletal disorders (MSDs) increases when poor working posture exist in combination with repetition and/or forceful exertion. In manual transfer activity, the distance between lifting origin and destination could affect workers’ exposure on poor lower back working posture. An experimental study was conducted to investigate the effect of transfer distance to lower back twisting and bending pattern in manual transfer activity. Positional body joints data of 26 male subjects were captured using the combination of motion capture (MOCAP) system with MVN studio software. Calculated data were plotted against time to track subjects’ lower back twisting and bending behavior. In general, longer the transfer distance would result in smaller twisting angle but higher bending angle. Statistical analysis in this study suggests 0.75m to 1.00m as the optimum transfer distance to balance lower back twisting and bending exposure on workers. This study is envisioned to provide insights for practitioners to consider space requirements for MMH activity to minimize lower back twisting and bending, and consequently the development of MSDs.